An essay on the agricultural production organization in former communist countries - Marian Rizov (The Social Science Journal, 2003)
This paper reviews and interprets existing information and transaction costs theories of firm organization and entrepreneur's role in order to provide a consistent explanation of the farm-sector dynamics in former communist countries. Important determinants of farm restructuring are economic factors, such as relative productivity of existing human and physical capital in different organizations, risk, terms of trade, transition specific distortions, and factor intensity of agricultural production. To a large extent, however, the phenomenon of various new enterprises being established represents not just general economic and policy conditions but also a diverse population of economic agents.
Keywords: Q18; Q13; 330; Production organisation; agriculture; Transition; institutions